Ectoparasitismo em aves silvestres em um fragmento de mata (Uberlândia, MG) - Pascoli, Graziela Virginia Tolesano (2005)
This work aimed: to determine the prevalence and the parasitic burden of ticks in wild birds; to identify the species of ticks found in those birds; to correlate the occurrence and the parasitic load of ticks with ecological variables of the hosts; and to determine the prevalence of feather mites and of chewing lices in the species of captured birds. The study was developed in a fragment of Forest of Gallery (30 there are), located in Fazenda Experimental do Glória (municipality of Uberlândia, State of Minas Gerais). Four field trips were accomplished, from March to June 2005. During 10 days of captures, 20 mist nets (12x2.6m) were open from sunrise to the sunset (2,000 hours/net). The parasites were searched by manual inspection and ticks were collected for identification. Prevalence, relative density and mean intensity of infestation were calculated. Diet, degree of forest dependence and participation in mixed flocks followed the literature. A total of 162 birds were captured (10 families, 22 genders and 26 species). The most frequent species were: Antilophia galeata (n=63 individuals), Eucometis penicilata (n=12) and Arremon flavirostris (n=11). Four endemic species of Cerrado were captured: Hylocryptus rectirostris, Antilophia galeata, Basileuterus leucophrys, Herpsilochmus longirostris. The overall prevalence rate for ticks was of 53% (86 individuals of 15 species, all of them Passeriformes). In the total, 352 ticks were collected. The identified species were: Amblyomma longirostre, Amblyomma nodosum and Rhipicephalus sanguineus. Only one adult tick were collected, and between the immature ticks 64% were in the larval stage (n=225). These larvae were attached mainly in the eyelids and head. Most of the species and of the individuals are forest dependent (n=14 species; 130 individuals). The frugivorous and forest dependent bird species were more infested. The species that participate in mixed flocks had a larger prevalence rate, however smaller parasitic load. The degree of forest dependence of the birds showed significant positive correlation with the prevalence rate (rs=0.6978; p=0.0001) and the relative density of ticks (rs=0.6779; p=0.0001). It was not found significant correlation between infestation and mixed flocks. Among 37 recaptured birds, 12 (32.4%) represented new cases of infestation by ticks and seven of re-infestation. The prevalence rate of feather mites was of 64% and the one of chewing lice of 13%. Several birds (n=48 individuals) were infested for more than one parasite type. The results show a high transmission level of ectoparasites in the area, maybe as consequence of the strong environmental pressure input over the forest fragment studied.